IMPLEMENTATION OF PANCASILA VALUES IN CREATIVE ACTIVITIES TO STRENGTHEN THE NATIONAL IDENTITY OF INDONESIAN CHILDREN IN MALAYSIA - Fitri Amaliah; Ryan Taufika; Zulkifli Amin; Cindy Safira; Miftha Huljannah; Juliaman Siahaan (Program Pascasarjana UIN Sumatera Utara, 2026)
In the era of globalization and increasing mobility of indonesian communities abroad, maintaining national identity has become a significant challenge for young generations of the diaspora. Education based on pancasila values serves as an essential means to cultivate national character from an early age, including through creative activities in non-formal learning environments. This study aims to analyze the implementation of pancasila values through creative activities in strengthening the national identity of indonesian migrant workers in malaysia. A qualitative approach with a case stduy design was conducted at sanggar belajar malaysia ( SBM ) through in- depth interviews, participatory obsevations, and documentation. The findings show that creative activities such as drawing pancasila values, hero literacy, educational board games, and crafting the indonesian flag effectively instill the values of mutual cooperation, tolerance and nationalism. The use of the indonesian language and the celebration of national holidays further strengthen the children's sense of patriotims. The sanggar belajar model has proven to be an effective medium for character education among diaspora children. This study recommend replicating this model in other diaspora communities and encouraging government policies to supprot pancasila-based character education abroad.